Internal pigment cells respond to external UV radiation in frogs - Franco-Belussi, Lilian [UNESP]; Sköld, Helen Nilsson; De Oliveira, Classius [UNESP] (The Company of Biologists, 2016)
Fish and amphibians have pigment cells that generate colorful skins important for signaling, camouflage, thermoregulation and protection against ultraviolet radiation (UVR). However, many animals also have pigment cells inside their bodies, on their internal organs and membranes. In contrast to external pigmentation, internal pigmentation is remarkably little studied and its function is not well known. Here, we tested genotoxic effects of UVR and its effects on internal pigmentation in a neotropical frog, Physalaemus nattereri. We found increases in body darkness and internal melanin pigmentation in testes and heart surfaces and in the mesenterium and lumbar region after just a few hours of UVR exposure. The melanin dispersion in melanomacrophages in the liver and melanocytes in testes increased after UV exposure. In addition, the amount of melanin inside melanomacrophages cells also increased. Although mast cells were quickly activated by UVR, only longer UVR exposure resulted in genotoxic effects inside frogs, by increasing the frequency of micronuclei in red blood cells. This is the first study to describe systemic responses of externalUVRon internal melanin pigmentation, melanomacrophages and melanocytes in frogs and thus provides a functional explanation to the presence of internal pigmentation.
Keywords: Anuran; DNA damage; Melanocytes; Melanomacrophages; Physalaemus nattereri; Solar radiation